2018
DOI: 10.3390/healthcare6030072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Skeletal Muscle and Fat Mass on Muscle Strength in the Elderly

Abstract: It is important for elderly people to maintain or improve muscle strength and for clinicians to know the factors that affect muscle strength. Therefore, the purpose of this study was to compare the effects of fat mass (FM) and skeletal muscle mass (SMM) on muscle strength. The participants included 192 community-dwelling elderly women. The SMM and FM, grip strength, and knee extension strength were measured. Data were evaluated using stepwise multiple linear regression analysis, which was performed with grip o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Each subject was barefooted, stood on the left and right metal plates, and grasped the metal conductor with both upper limbs for measurement. Quantitative evaluation of the skeletal muscle mass by the BIA method using Inbody is reliable and valid [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Each subject was barefooted, stood on the left and right metal plates, and grasped the metal conductor with both upper limbs for measurement. Quantitative evaluation of the skeletal muscle mass by the BIA method using Inbody is reliable and valid [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Lean mass was significantly associated with grip strength [23]. Fat mass was positively associated [24], negatively associated [25], or not associated [26].…”
Section: Introductionmentioning
confidence: 86%
“…Sherk et al [24] reported that fat mass was significantly correlated with upper muscle strength in postmenopausal women. On the other hand, a previous study reported that fat mass of the upper limbs was negatively associated with grip strength in the elderly [25]. Moreover, Ibeneme et al [26] demonstrated that there was no significant correlation between fat mass and grip strength in postmenopausal women.…”
Section: Table 2 Mean (Sd) Of Stiffness Index According To Fat Mass A...mentioning
confidence: 93%
“…However, their function may decrease with age, as the skeletal muscle mass (SMM) of a 70‐year‐old man has been reported to be approximately 15% lower than that of a 20‐year‐old adult 4 . A decrease in SMM is associated with a decrease in grip strength, which suggests that a decrease in muscle mass is associated with a decrease in muscle function 5 . SMM is widely recognised as a predictor of health impairment and decreased activities of daily living (ADL) 6 .…”
Section: Introductionmentioning
confidence: 99%
“…4 A decrease in SMM is associated with a decrease in grip strength, which suggests that a decrease in muscle mass is associated with a decrease in muscle function. 5 SMM is widely recognised as a predictor of health impairment and decreased activities of daily living (ADL). 6 This indicates that ageing is one of the causes of decrease in muscle mass.…”
mentioning
confidence: 99%